New Insights Into the Role of Qa-2 and HLA-G Non-classical MHC-I Complexes in Malignancy - da Silva, Istéfani L.; Montero-Montero, Lucía; Ferreira, Enio; Quintanilla, Miguel (Frontiers in Immunology, 2018)
It is well established that the immune system can identify and destroy neoplastic transformed cells in a process known as immunosurveillance. Most studies have focused on the classical major histocompatibility complex (MHC) class Ia molecules, which are known to play an important role on the presentation of tumor antigens to the immune system in order to activate a response against tumor cells. However, a larger family of non-classical MHC class Ib-related molecules has received less attention. In this mini-review, we discuss the role of class Ib murine Qa-2 and its proposed human HLA-G homolog on immunosurveillance during embryogenesis and cancer. Whereas both HLA-G and Qa-2 are involved in immune tolerance in pregnancy, they play opposite roles in cancer. HLA-G appears to promote tumor progression while Qa-2 acts as a tumor suppressor awaking the immune system to reject tumor cells, as suggested by studies on different cancer cell models, such as melanoma, lymphoma, lung carcinoma, and our own results in mammary carcinoma.